Response to active hepatitis B vaccination and mortality in incident dialysis patients. Issue 5 (1st February 2017) - Zitt, Emanuel; Hafner-Giessauf, Hildegard; Wimmer, Birgitta; Herr, Alexander; Horn, Sabine; Friedl, Claudia; Sprenger-Mähr, Hannelore; Kramar, Reinhard; Rosenkranz, Alexander R.; Lhotta, Karl
Highlights: Hepatitis B vaccination response associated with survival in incident dialysis patients. Seroconversion and seroprotection associated with better survival. Simple and readily available tool to estimate independent dialysis patient survival. Abstract: All patients with advanced chronic kidney disease or on renal replacement therapy should receive active hepatitis B vaccination. The aim of this retrospective cohort study was to investigate the association between the immune response to hepatitis B vaccination and all-cause, cardiovascular or infection-related mortality in incident dialysis patients starting dialysis between 2001 and 2008 (n = 426) in two Austrian dialysis centers. Vaccination response was defined as follows: absent anti-HBs antibody titer or a titer <10 IU/L was classified as non-response, seroconversion (SC) was defined as a titer ⩾10 IU/L, and seroprotection (SP) as a titer ⩾100 IU/L. Kaplan-Meier survival curves and multivariable adjusted Cox Proportional Hazards Models were used to determine the association between vaccination response and all-cause, cardiovascular and infection-related mortality. Of all patients 207 (48.6%) were non-responders, SC was observed in 219 (51.4%), SP in 118 (27.7%) patients. During a median follow-up of 51.2 months 228 (53.5%) patients died. Patients with SP and SC showed a significantly lower all-cause (p < 0.001 for both) and cardiovascular mortality (p = 0.006 for SP, p = 0.01 for SC). SP and SC were independently associated with a significant risk reduction for all-cause mortality (SP: HR 0.69, 95% CI 0.49–0.97, p = 0.03; SC: HR 0.72, 95% CI 0.55–0.95, p = 0.02). In conclusion, achieving seroconversion and seroprotection after active hepatitis B vaccination is associated with significantly reduced all-cause mortality in incident dialysis patients. This simple and readily available tool allows estimation of patient survival independently of other well-known key parameters such as age, gender, the presence of diabetes and markers of malnutrition and inflammation.